2014
DOI: 10.1093/carcin/bgu189
|View full text |Cite
|
Sign up to set email alerts
|

Clinical potential role of circulating microRNAs in early diagnosis of colorectal cancer patients

Abstract: Current procedures for diagnosis and biomarker examination of colorectal cancer (CRC) are invasive and unpleasant. There is a great need to identify sensitive and specific biomarkers for early diagnosis of CRC. Circulating microRNAs (miRNAs) are promising molecular markers for CRC prediction. We performed a comprehensive meta-analysis to integrate an evaluation index for diagnostic accuracy of circulating miRNAs in diagnosing CRC patients. Furthermore, we conducted an independent validation set of 49 CRC patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 41 publications
2
43
0
Order By: Relevance
“…The morbidity rate of colorectal cancer is gradually rising and its malignant biological behavior is closely associated with a small group of tumor stem cells (19). Early-stage diagnosis of colorectal cancer can be missed and in later stages, distant metastasis may occur, together resulting in a poor patient prognosis (20). Therefore, investigations into the molecular mechanism of the occurrence and development of colorectal cancer can aid the prophylaxis and treatment of colorectal tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity rate of colorectal cancer is gradually rising and its malignant biological behavior is closely associated with a small group of tumor stem cells (19). Early-stage diagnosis of colorectal cancer can be missed and in later stages, distant metastasis may occur, together resulting in a poor patient prognosis (20). Therefore, investigations into the molecular mechanism of the occurrence and development of colorectal cancer can aid the prophylaxis and treatment of colorectal tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported on the potential of circulating plasma/serum miRNA as a diagnostic biomarker for CRC patients using various kinds of miRNA [9,10,20,21]. In this study, firstly, we clarified the microarray-based miRNA expression profiles of exosomes separated from the plasma of CRC patients.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, several papers have reported the usefulness of plasma/serum miR-21 levels as a biomarker for diagnosis in CRC patients [23,24,25,26,27,28]. However, the clinical significance of plasma/serum miRNA as a biomarker for diagnosis is still controversial, and some papers have indicated that serological miR-21 does not have any impact on diagnosis in CRC patients [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 A number of studies have also reported the presence of miRNAs in high concentrations in body fluids and stool of patients with CRC. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] These miRNAs could potentially act as novel biomarkers for noninvasive diagnosis of CRC. Most of these miRNAs were identified using standard methods of microarray and real-time reverse transcription-polymerase chain reaction (RT-PCR) approaches.…”
mentioning
confidence: 99%